Commonality: A longitudinal study - VELU, Raja (Institutional Knowledge at Singapore Management University, 2018)
The commonality in the asset characteristics such as returns, liquidity and other non-trade parameters attracted intense research interest in the literature. In this paper, we investigate the longitudinal trend in commonality for the duration 2000-2016, an extensive that include years of boom and bust in the financial market. Our results show that while market has become more fragmented, commonality in returns has doubled over this period. This observation holds across all exchanges, with a clear trend of convergence in exchange-wide commonality over time due to increased information efficiency. We develop a unified methodology to systematically accommodate all explanatory factors for commonality. Finally, we show that incorporating commonality into standard microstructure models leads to a significant improvement in their explanatory power.